Charged Particles Multiplicity and Scaling Violation of Fragmentation Functions in Electron-Positron Annihilation - Tooraj Ghaffary (Advances in High Energy Physics)
By the use of data from the annihilation process of electron-positron in AMY detector at 60 GeV center of mass energy, charged particles multiplicity distribution is obtained and fitted with the KNO scaling. Then, momentum spectra of charged particles and momentum distribution with respect to the jet axis are obtained, and the results are compared to the different models of QCD; also, the distribution of fragmentation functions and scaling violations are studied. It is being expected that the scaling violations of the fragmentation functions of gluon jets are stronger than the quark ones. One of the reasons for such case is that splitting function of quarks is larger than splitting function of gluon.